Assessment of hydrogen production methods via integrated MCDM approach under uncertainty - Seker, Sukran; Aydin, Nezir (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Energy has a crucial role for the existence and social well-being of human. Among various options, hydrogen is the promising energy carrier for sustainable energy systems. As an important source of hydrogen, Hydrogen Sulphide (H2S) is abundantly found in Black Sea waters and known as an environmental pollutant. The main aim of this study is to evaluate Thermochemical, Electrochemical, Thermal, Photochemical, Plasma, and Thermal methods as decomposition methods, which meet sustainability aspects better than other technologies, based on expert opinions. As sustainable criteria, economically feasibility, ecologically feasibility, efficiency, process simplicity, energy requirement, safety and reliability, applicability and operational suitability and technical maturity are considered to determine the most appropriate hydrogen production method. In this sense, we have suggested a new integrated Multi-Criteria-Decision-Making (MCDM) methodology consisting of stepwise weight assessment ratio analysis (SWARA) with fuzzy set theory (FST) and Weighted Aggregated Sum Product Assessment (WASPAS) by employing interval valued intuitionistic fuzzy sets (IVIFS) in the selection process. The contribution of the study is not only proposing a new method which hybridizes the SWARA and WASPAS under uncertainty but also selecting the most sustainable Hydrogen production method utilizing from H2S in the Black Sea in Turkey, considering sustainable criteria which are unavoidable in energy management problems. At the end, the results are discussed, and sensitivity and comparative analyses are utilized to check the robustness and feasibility of solutions. Consequently, electrochemical is selected as the best and most appropriate hydrogen production method in terms of providing high efficiency in conversion and sustainable processes, i.e handling, transporting and storing harmful chemicals. (c) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen energy; Hydrogen production methods; Sustainability; Sensitivity and comparative; analyses; GROUP DECISION-MAKING; BLACK-SEA; MULTICRITERIA EVALUATION; ENERGY; SELECTION; SULFIDE; TECHNOLOGIES; EFFICIENCY; EXTENSION; Chemistry; Electrochemistry; Energy & Fuels